Halal And Haram Food In Islam: Science Perspective - Muhammad Ridho; Ayu Anggraini; Yoli Oktaviani (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
Halal and haram food is essential for the public to pay attention to Al-Quran and Hadith have regulated halal and haram food. Obeying the prohibition not to consume haram food is believed to contain wisdom and goodness for Muslims. Likewise, in science and technology, there are increasingly rapid developments. Almost all aspects have been modernized, including research in Islamic elements. Many studies have concluded the facts regarding the causes of food that Islamic law prohibited or prohibited. This research will discuss scientific reasons that haram food harms human health. Discussed the procedures for slaughtering by the Shari'a to classify the animal as halal for human consumption. This research refers to the primary sources of Islamic law, namely the Al-Quran and Hadiths, and scientific studies that prove the negative impact of haram food on human health. Based on this research, many causes are not suitable for consumption. They can endanger human health, such as the presence of harmful bacteria in carcasses, toxic compounds in blood, parasitic diseases in pigs, organ damage due to consumption of Khamr, and the dangers of consuming unprocessed meat. slaughtered according to Islamic law